Seven-dimensional considerations of Einstein's connection. II. The recurrence relations of the second and third kind in 7-g-UFT - Mi Ae Kim; Keum Sook So; Chung Hyun Cho; Kyung Tae Chung (International Journal of Mathematics and Mathematical Sciences)
We present powerful recurrence relations of the second and third kind which hold in 7-dimensional Einstein's generalized Riemannian manifold X7. All considerations in this paper are restricted to the first and second classes of X7 only since the case of the third class, the simplest case, was already studied by many authors.